Reception studies and audiovisual translation - Di Giovanni, Elena; Gambier, Yves, 1949- (Benjamins translation library, 2018)
"The coming of age of audiovisual translation studies has brought about a much-needed surge of studies focusing on the audience, their comprehension, appreciation or rejection of what reaches them through the medium of translation. Although complex to perform, studies on the reception of translated audiovisual texts offer a uniquely thorough picture of the life and afterlife of these texts. This volume provides a detailed and comprehensive overview of reception studies related to audiovisual translation and accessibility, from a diachronic and synchronic perspective. Focusing on all audiovisual translation techniques and encompassing theoretical and methodological approaches from translation, media and film studies, it aims to become a reference for students and scholars across these fields."--